Impacts of COVID-19 Crisis on Private Equity Funds in Emerging Markets - Strusani, Davide; Verma, Priyanka; Manenti, Giorgio (International Finance Corporation, Washington, DC, 2021)
The role traditionally played by Private Equity Fund (PE Fund) investments in supporting private sector development in Emerging Markets (EMs) is being challenged by the COVID-19 pandemic. This note assesses how PE Funds in EMs may evolve as a result of the COVID-19 crisis, focusing on the Growth Equity and Venture Capital (VC) asset classes. Growth Equity funds, which focus on accelerating investees’ growth through operational enhancements, account for a significant share of PE Fund investments in several developing regions, while VC funds are a fast-growing vehicle in certain EMs and present specific opportunities related to technology and digitization in the context of the COVID-19 crisis. This note also discusses how selected ‘megatrends’ may impact these two asset classes in the medium term, along with opportunities for the industry and for enhanced DFI support. The intended audience for this note is international development practitioners, private equity professionals in emerging markets, and capital market analysts.